A Public International Law approach to safeguard nationality for surrogate-born children. (2nd January 2018) - Ghráinne, Bríd Ní; McMahon, Aisling
Abstract : International surrogacy agreements involve a child born to a surrogate mother who is of a different nationality to the commissioning parent(s) in a state other than that of which the commissioning parent(s) are nationals or reside. Many of these arrangements lead to children being born stateless, which deprives that child of many rights that are directly linked to one's nationality as well as causing significant practical problems, such as difficulty in obtaining a passport. In undertaking the first Public International Law analysis of nationality and international surrogacy agreements, we map out how various provisions can be used to guarantee protections against statelessness. Accordingly, we argue that the drafting of a proposed new convention is not the ideal solution in this respect, and should not be to the detriment of the ratification and implementation of the relevant conventions that we identify; in particular, the 1989 Convention on the Rights of the Child. We argue that these protections offer the most meaningful protection in the short term and should be used to inform any future protections under the proposed Convention. We conclude by encouraging the advancement of Public International Law arguments when petitioning in a domestic context on behalf of stateless international surrogate children.